SARS-CoV-2-derived RNA replicons as safe and effective vaccines - Marta Villarejo-Torres; Iván Nombela-Diaz; Diego Muñóz-Santos; Mercedes Ruiz-Yuste; Ana Marchena-Pasero; María A. Rueda-Huélamo; Jorge Ripoll-Gómez; Pedro J. Sánchez-Cordón; Laura Fernandez del Ama; José M. Honrubia; Javier Gutiérrez-Álvarez; Jesús Hurtado-Tamayo; et al. (Proceedings of the National Academy of Sciences, 2025)
A collection of RNA replicons (RRs) derived from severe acute respiratory syndrome 2 (SARS-CoV-2) for use in vaccine design was constructed by genetic engineering using bacterial artificial chromosomes. A replicon, which was deleted in six genes (3a, 3c, E, 6, 7a, and 7b) was selected. Cells infected with the RR vaccine candidate led to the formation of virus-like particles that, due to the failure of being secreted, increase vaccine safety, in contrast to the wild type virions. The replicon maintained the production of RNAs encoding at least proteins S, M, and N for several days. Intranasal immunization with the RR of transgenic mice, expressing human ACE2, elicited respiratory mucosal immunity. Immunization protected against challenge with SARS-CoV-2, inducing IgG, IgM, and IgA antibodies to the spike (S) protein, the receptor binding domain, N and M proteins, and cellular immune responses (CD4 + , CD8 + , and long-term memory T cells). Coinfection of cells with the RR vaccine and a full-length SARS-CoV-2 led to a significant inhibition of replication of full-length virus, increasing the safety of the RR vaccine. The RR vaccine induced a minor inflammatory reaction in the absence of major side effects and was stable at different temperatures. An updated RR expressing XBB.1.5 S protein elicited neutralizing antibodies against the homologous virus and provided full protection against recent SARS-CoV-2 variants.